PEMBERDAYAAN PETANI UNTUK MENUNJANG PEMBANGUNAN PERTANIAN - Windia, Wayan (PIRAMIDA; Vol. 1, No. 1 April 2005)
Agricultural development need impowered farmers. Based on those farmers, the farmers will know their problems, and the solution of its problems. Beside that, the farmers also will know how to use any resources in its surroundings, in order to stimulate the agricultural development or their prosperity. In relation with how to get impowered farmers, so the all stackholders  especially the government need more attention to the agricultural sektor and farmers. Basically, the impowerment of farmers is a cultural activities. If its assumption is true, so to be needed the activities on thinking pattern, sosial, and artefax respetively.
Keywords: former empowerment, agricultural development, cultural activities